An Analysis for IDH‐Mutant Grade 4 Astrocytoma Based on WHO CNS 5: Implication of Clinical Practice - Xianxin Qiu; Liping Liang; Lingchao Chen; Pengjie Hong; Wanzun Lin; Jiabing Liu; Zhirui Zhou; Wenjia Zhu; Tianqi Wu; Mingyuan Pan; Yihua Zhong; Jing Gao; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Purpose There is ongoing debate regarding the therapeutic approach and prognosis for IDH‐mutant grade 4 astrocytoma, a newly defined subtype of diffuse glioma in the 2021 WHO classification system for central nervous system tumors (WHO CNS 5). The aim of this study was to explore the clinical outcome and prognosticators for newly diagnosed IDH‐mutant grade 4 astrocytoma based on our single institutional data. Methods This retrospective analysis included 53 consecutive patients with newly diagnosed IDH‐mutant grade 4 astrocytoma, who underwent radiotherapy between September 2021 and December 2023. All patients were administered concurrent and adjuvant temozolomide. Eleven patients received adjuvant tumor‐treating fields (TTFields). Results The median follow‐up was 15.7 months. Twenty patients had tumor relapse; three patients died, all of whom were without TTFields therapy. The median PFS for the entire cohort was 19.3 months, and the median OS was not reached. Univariate analysis indicated patients younger than 40 years (p = 0.11) or without homozygous deletion of CDKN2A/B (p = 0.11) tended to have better PFS. In addition, the TTFields group tended to have longer median PFS than the non‐TTFields group in both analyses before and after propensity score matching (PSM) (24.4 vs. 18.5 months, p = 0.097, before PSM; 24.4 vs. 15.9 months, p = 0.080, after PSM). No significant independent prognostic factor was found in the multivariate analysis. Conclusions The study reveals important insights into clinical practice for IDH‐mutant grade 4 astrocytoma. Younger age and tumor without deleted CDKN2A/B might be predictive of better outcomes. The addition of TTFields trended towards improved PFS, necessitating prospective clinical trials for further investigation.